2018
DOI: 10.3390/socsci7050078
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Volunteering and Life Satisfaction in Midlife and Old Age: Findings from 12 European Countries

Abstract: A growing literature shows that doing voluntary work not only helps the wider community but can also improve one's own well-being. To date, however, few studies have examined the relationship between volunteering and well-being in non-US and especially in comparative data. We study this relationship using two waves of data of 18,559 individuals aged 50 and above from 12 European countries. We analyze life satisfaction impacts of change and stability in volunteering status and in the intensity (frequency) of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 39 publications
7
60
0
1
Order By: Relevance
“…The findings of the study further suggested that engaging in voluntary work allowed the volunteers to achieve greater meaning in life, as is consistent with other studies (Binder, 2015; Hansen, Aartsen, Slagsvold, & Deindl, 2018). The participants herein were generally retirees at least 61 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the study further suggested that engaging in voluntary work allowed the volunteers to achieve greater meaning in life, as is consistent with other studies (Binder, 2015; Hansen, Aartsen, Slagsvold, & Deindl, 2018). The participants herein were generally retirees at least 61 years of age.…”
Section: Discussionsupporting
confidence: 90%
“…The responses showed that voluntary work is carried out because of a personal and humanistic motive and satisfaction as a result of feeling responsible towards others. This result supports what (Hansen et al, 2018) mentioned regarding voluntary work claiming that itis a common feeling that increases relationships and solidarity with others in addition to increasing their trust in the institution they belong to. Moreover, voluntary work organizes their efforts and increases their skills and efficiencies during training (Aranda et al, 2019;René Bekkers, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, participants in the experimental group created useful products that could be sold for charity reasons or given as gifts. Previous research shows that voluntary work, such as the ones included in this comprehensive active aging program, promote a strong sense of meaning and personal growth, thus they have a positive influence on older adults' psychological well-being and life satisfaction (Hansen, Aartsen, Slagsvold, & Deindl, 2018;Ho, 2017;Pilkington, Windsor, & Crisp, 2012).…”
Section: Discussionmentioning
confidence: 99%